Probability of Deuterium Atom Electrons in Momentum Space at Quantum Numbers n 3 - Supriadi*, Bambang; Lorensia, Sinthia Lolita; Shahira, Firda; Prabandari, Audri Mely; Putri, Aurellya Abdillah Wijaya (Graduate School of Universitas Syiah Kuala, 2023)
Deuterium is one of the isotopes of the hydrogen atom, which consists of 1 proton, 1 neutron, and 1 electron, also called a hydrogenic atom. The position of electrons in the atom cannot be determined with certainty because it is probabilistic. The probability of finding a deuterium atom electron in momentum space at quantum number n 3. This research aims to find the probability value of deuterium atomic electrons in momentum space at n 3. This research uses the mathematical theory study method through several stages, namely collecting the latest and relevant literature sources, making a simulation program, and then validating the simulation program with existing theory. If it has been validated, continue taking data that will be analyzed and then discussed in the results and discussion stage, and the last step is drawing conclusions. The results of this study show that the probability value for finding atomic electrons in momentum space will be more excellent with increasing integration limit values and the value of the principal quantum number (n).